Comparison of cytokinin-binding proteins from wheat and oat grains - Kamínek, Miroslav; Trcková, Marie; Fox, J. Eugene; Gaudinová, Alena (Physiologia plantarum, 2003)
Cytokinin-binding proteins (CBPs) isolated from mature grains of oat (Avena sativa L.) and wheat (Triticum aestivum L.) by acid precipitation, ion-exchange and affinity chromatography had similar characteristics, although they differed somewhat in apparent molecular weight of the native protein as determined by gel filtration (109 and 133 kDa, respectively) and subunit size as estimated by SDS-polyacrylamide gel electrophoresis (47 and 55 kDa, respectively). Highly purified oat CBP showed very weak but distinct immunochemical cross-reactivity with anti-wheat CBP IgG, indicating different immunogenic properties of the two CBPs. Nevertheless, both CBPs exhibited very similar binding of different cytokinins and were characterized by high affinity for N6-benzyladenine (BA)-type and by low affinity for zeatin-type cytokinins to both wheat and oat CBPs and by somewhat higher binding activities of oat CBP compared to wheat CBP (Kds for BA: 4.6 x 10-7 M and 6.8 x 10-7 M, respectively). The potential role of CBPs in regulating free BA-type cytokinin levels during cereal grain development and germination is discussed.